S09-2 The impact of mass-media campaigns on physical activity: a review of reviews through a policy lens. (29th August 2022) - den Braver, Nicolette R; Bengoechea, Enrique Garcia; Messing, Sven; Kelly, Liam; Schoonmade, Linda J; Volf, Kevin; Zukowska, Joanna; Gelius, Peter; Forberger, Sarah; Woods, Catherine; Lakerveld, J; ,
Abstract: Background: This review of reviews aims to summarize the evidence from published reviews on the effectiveness of mass-media campaigns to promote physical activity (PA), or PA-related determinants, and identify policy-relevant recommendations related to successful PA campaigns. Methods: An extensive literature search was performed on March 1st, 2021. Reviews that evaluated the impact of campaigns on distal (e.g., PA) and/or proximal outcomes of PA (awareness, knowledge etc.) and that targeted the general population or subsets were included. Quality of reviews was assessed using the AMSTAR-2 tool. Policy-relevant recommendations were systematically derived and synthesized, and formulated as good practice statements. A protocol was registered beforehand (ID: CRD42021249184). Results: A total of 1, 915 studies were identified, of which 22 reviews were included. Results indicate that the most consistent evidence was found for the effectiveness of mass-media campaigns on proximal outcomes, while the evidence for distal outcomes was mixed. Good practice statements were derived: 1) to achieve behaviour change, mass-media is an important component of larger, multilevel, and multicomponent strategies, 2) mass-media strategies should be coordinated and aligned at local- and national-level, and be sustained, monitored and resourced at these levels, 3) media should be tailored to reduce socioeconomic inequalities. Conclusions: Mass-media can play an important role in the promotion of PA. In general, evidence was more inconsistent for effectiveness on distal outcomes than for proximal outcomes. The policy-relevant recommendations identified will serve to inform the PA environment policy index (PA-EPI), a tool for monitoring, evaluating and benchmarking government progress in implementing public policies.